PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN SAAT PANDEMI COVID 19 DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PEUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Hafidz Rully Amirullah; Fitra Dharma; Widya Rizki Eka Putri (Universitas Widyatama, 2021)
This study analyzed the value of the company during the Covid 19 pandemic using LQ45 companies as the sample. This study aims to find out how the condition of the LQ45 firm value during the covid 19 pandemic during 2020. The data and information used in this study were obtained from the website of Indonesia stock exchange. This study used quantitative research methods. The independent variables used in this study were Intellectual capital, profitability as a moderating variable, and firm size as a control variable.The data used was secondary data in the form of audited annual financial reports obtained from the Indonesia Stock Exchange (IDX) website. Based on the results of the analysis of intellectual capital research that has a positive effect on firm value during the covid 19 pandemic, the profitability variable as a moderating variable can moderate the relationship between intellectual capital and firm value during the covid 19 pandemic, the firm size variable as a control variable has no effect on the firm value of LQ45 during the covid19 pandemic.